(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
It is no secret that today in Uzbekistan, attention to art and culture is considered the main criterion of social reform. Decrees and resolutions issued by the Government of the Republic of Uzbekistan in recent years directly contribute to the further development of the arts and culture. It is known from history that the level of development of any society is determined by the development of art and culture in that society.